2018
DOI: 10.3389/fneur.2018.01108
|View full text |Cite
|
Sign up to set email alerts
|

The Early Developmental Outcomes of Prenatal Alcohol Exposure: A Review

Abstract: Aim: This paper systematically reviews the literature on the effects of prenatal alcohol exposure on early child development from birth to 5 years with the aim to synthesize the developmental outcomes associated with prenatal alcohol exposure, and inform further research to improve our knowledge of the manifestations of prenatal alcohol exposure.Methods: Electronic databases (MEDLINE, Psych INFO, and Psych ARTICLES) were searched to find papers on the developmental outcomes of prenatal alcohol exposure in neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 139 publications
(270 reference statements)
1
33
0
1
Order By: Relevance
“…Next, there is evidence of delays in motor skills and language with heavy PAE but less evidence with light PAE. A review by Subramoney et al (2018) concluded heavy PAE was associated with impaired motor skill development in young children, and other reviews have drawn similar conclusions for older children (Bay & Kesmodel, 2011;Doney et al, 2014). The association is less certain for light to moderate PAE (Hutchinson et al, 2019).…”
mentioning
confidence: 91%
“…Next, there is evidence of delays in motor skills and language with heavy PAE but less evidence with light PAE. A review by Subramoney et al (2018) concluded heavy PAE was associated with impaired motor skill development in young children, and other reviews have drawn similar conclusions for older children (Bay & Kesmodel, 2011;Doney et al, 2014). The association is less certain for light to moderate PAE (Hutchinson et al, 2019).…”
mentioning
confidence: 91%
“…Alcohol consumed by a pregnant woman can easily cross the placenta, and increases fetal blood alcohol concentrations to the levels equivalent to those in maternal side within 2 h of ingestion (Burd et al, 2012). Affected individuals of FASD display a spectrum of defects, including facial malformations and neurobehavior impairments (Subramoney et al, 2018).…”
Section: Alcoholmentioning
confidence: 99%
“…The severity of any of these outcomes depends on the level and gestational pattern of alcohol exposure and is also likely influenced by other maternal factors, such as nutrition, stress and genetics, as well as the postnatal psychosocial environment. Despite many longitudinal studies focussing on this topic, recent systematic reviews still find that the literature on child outcomes with lower levels of exposure is inconclusive [1][2][3]. The ongoing debate of whether there is a 'safe' level of alcohol use in pregnancy has resulted in many official guidelines applying the precautionary principle and recommending complete abstinence in pregnancy.…”
Section: Introductionmentioning
confidence: 99%